2022
DOI: 10.1007/s00431-022-04514-8
|View full text |Cite
|
Sign up to set email alerts
|

Young children with a minor traumatic head injury: clinical observation or CT scan?

Abstract: Currently, in young children with minor traumatic head injuries (MTHI) classified as intermediate risk (IR), PECARN recommends clinical observation over computer tomography (CT) scan depending on provider comfort, although both options being possible. In this study, we describe clinicians’ choice and which factors were associated with this decision. This was a planned sub-study of a prospective multicenter observational study that enrolled 1006 children younger than 18 years with MTHI who presented to six emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This examination is recommended in cases of persistent or worsening neurological disorders, focal neurological signs or obvious brain injury, to search for bone and brain lesions [12]. Some studies have shown, however, that other criteria that may influence the achievement of CT in the case of head-brain injury, namely an age greater than 2 years and the occurrence of trauma during the weekend [13].…”
Section: Discussionmentioning
confidence: 99%
“…This examination is recommended in cases of persistent or worsening neurological disorders, focal neurological signs or obvious brain injury, to search for bone and brain lesions [12]. Some studies have shown, however, that other criteria that may influence the achievement of CT in the case of head-brain injury, namely an age greater than 2 years and the occurrence of trauma during the weekend [13].…”
Section: Discussionmentioning
confidence: 99%
“…TBI severity in clinic has been classified as mild, moderate and severe using the patient’s level of consciousness measured by the Glasgow Coma Scale (GCS) ( McKee and Daneshvar, 2015 ). Adult patients presenting with low GCS scores and/or suspected intracranial hemorrhage, often undergo computed tomography (CT), but head CT scans in young children are prescribed with caution because of potential risks of ionizing radiation on developing brain ( Niele et al, 2022 ). Overall, TBI affects about three million children worldwide each year ( Dewan et al, 2016 ).…”
Section: Pediatric Traumatic Brain Injurymentioning
confidence: 99%
“…The secondary outcomes were to compare the rate of traumatic brain injuries in the two groups and to identify factors that were potentially associated with the risk of clinically important traumatic brain injuries. Because PECARN states that there are only clear-cut indications for neuroimaging for high-risk patients, 7,16 we limited our analysis of the latter secondary outcome to high-risk patients.…”
Section: Outcome and Analysesmentioning
confidence: 99%